Tense Interpretation of Verb Tenses in English and Uzbek Language - Muxabbat Sayilova (Scientific Trends, 2025)
This article analyzes the differences and similarities between English and Uzbek verb tenses. Verb tenses are one of the most important grammatical elements of every language, and the study of them is of great importance in language learning. Knowledge of the difference between the verb tenses in English and Uzbek, will help to form the correct understanding in the translation and study of the language.
Keywords: English, Uzbek language, verb tenses, grammar, similarities, differences.